Pierre Cardin Trademark Dispute - Atikah, Nisrina (Jurnal Mulawarman Law Review, 2019)
Trademark is a mark of commodity or service origin indentification which related with its producers. Trademark function is not only to differ a commodity with another commodity, but it has function as priceless company asset, especially for well-known mark. A trademark which became famous will make that trademark becomes valuable assets or properties of the company, but in the other side, the fame will lure other producers to run unfair business to commit “piracy” or imitate it. One of it happens on trademark dispute on case decision No.1 557K/Pdt.Sus-HKI/2015. This research research is to know protection toward well-known mark and PIERRE CARDIN LOGO are reviewed by normative intstrument which is Law No. 15, 2001 and TRIPs Agreement along with juridical concequence of Supreme Court Decision No.1 557K/Pdt.Sus-HKI/205 toward well-known mark in Indonesia. The method used in this research is normative research with law and conceptual approaches. This research uses primary law material and secondary law material, then the law materials are analyzed qualitatively and served prespectively. Research shows that: 1) Determination of court decision by the council of judges was according to valid law which is Law No. 15, 2011 regarding trademark but TRIPS Agreement aspect is not noticed entirely, justice and prosperity aspects which must consider economy and morale loss impacts by the user or owner of that well-known mark; 2) Juridical Consequence from decision No.557K/Pdt.Sus-hki/2015 is well-known marks which are enter to Indonesia must follow indonesia national law, even though sutantively it was registered in several countries and obtained fame globally.